Journey of forgiveness: Forgiveness therapy for orphaned adolescents - Wijaya, Daniswara Agusta; Widyorini, Endang (Universitas Mercu Buana Yogyakarta, 2023)
Female adolescents living in orphanages mostly have experienced adverse childhood experiences (ACEs) affecting their lifetime development. In order to recover from ACEs exposure, individual should be going through forgiveness. Hence, the intervention of this study aims to elicit forgiveness and investigate its effect on psychological well-being. There are 15 female orphaned adolescents participating in this study and experiencing at least one ACEs using convenience sampling. Intervention in the form of the Forgiveness Therapy module consists of three main sessions and two follow-up sessions. Measures toward changes in emotional forgiveness were conducted at three time points, and measures on psychological well-being were conducted at two time points. In addition to the Emotional Forgiveness Scale and Psychological Well-Being as quantitative measures, qualitative data were also collected. Results from repeated measure ANOVA showed positive effect of this intervention toward emotional forgiveness over time. Meanwhile, there is no significant improvement in psychological well-being even though the time difference between measures was set more significantly than the measures on emotional forgiveness